2021
DOI: 10.1002/adma.202007650
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Understanding of the Thriving Ambient Electrochemical Nitrogen Reduction Reaction

Abstract: The electrochemical method of combining N2 and H2O to produce ammonia (i.e., the electrochemical nitrogen reduction reaction [E‐NRR]) continues to draw attention as it is both environmentally friendly and well suited for a progressively distributed farm economy. Despite the multitude of recent works on the E‐NRR, further progress in this field faces a bottleneck. On the one hand, despite the extensive exploration and trial‐and‐error evaluation of E‐NRR catalysts, no study has stood out to become the stage prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
269
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(270 citation statements)
references
References 309 publications
1
269
0
Order By: Relevance
“…Although the mechanisms of CO 2 and N 2 reduction are still not conclusive, numerous studies have shown that defects and heteroatom dopants (e.g., N, B, P) can modify the band gap, charge distribution, and spin density of graphene and thereby boost the catalytic activity and selectivity toward CO 2 and N 2 reductions. [122][123][124][125][126][127] Graphene-supported metal nanoparticles and single-atom catalysts have also been proven as promising electrocatalysts for CO 2 and N 2 reductions. [128][129][130][131][132] Given the flexibility to tailor the topological defects and chemical dopants and to host nanoparticulate and single-atom metal catalysts, the 3D continuously porous graphene shows great promise for applications in electrochemical CO 2 and N 2 reductions with rationally optimized performance.…”
Section: Electrochemical Co 2 Reduction and N 2 Reductionmentioning
confidence: 99%
“…Although the mechanisms of CO 2 and N 2 reduction are still not conclusive, numerous studies have shown that defects and heteroatom dopants (e.g., N, B, P) can modify the band gap, charge distribution, and spin density of graphene and thereby boost the catalytic activity and selectivity toward CO 2 and N 2 reductions. [122][123][124][125][126][127] Graphene-supported metal nanoparticles and single-atom catalysts have also been proven as promising electrocatalysts for CO 2 and N 2 reductions. [128][129][130][131][132] Given the flexibility to tailor the topological defects and chemical dopants and to host nanoparticulate and single-atom metal catalysts, the 3D continuously porous graphene shows great promise for applications in electrochemical CO 2 and N 2 reductions with rationally optimized performance.…”
Section: Electrochemical Co 2 Reduction and N 2 Reductionmentioning
confidence: 99%
“…Electrochemical Nitrogen Reduction (ENR) Ammonia is greatly significant to industries and humankind in general. Global NH 3 production got as far as 146 million tons in 2015, and by the year 2050, it is likely to increase by 40% [ 166 ]. Over 80% of NH 3 total production is used for fertilizers which help sustain lives worldwide [ 167 ].…”
Section: Salient Applications Of 2d Materialsmentioning
confidence: 99%
“…[112] One may also consider using another type of membrane, such as Celgard 3501, which is low cost and has low NH 3 adsorption. [112] Apart from the typical H cell system, a traditional salt bridge (KCl) can be used as an alternative since it prevents NH 3 diffusion while maintaining the charge balance (Figure 4d). [111] The Bi-based materials, such as bismuth oxyhalides (BiOX), bismuth oxides, bismuth polyoxometalates (Bi-POMs), and bismuth subcarbonates, are mostly investigated in the PC system for NRR studies, owing to their suitable optical properties and tunable structures.…”
Section: Systems For Nrrmentioning
confidence: 99%